Asymmetric Michael reaction catalyzed by mimicked peptides - Bayat, Saadi; Tejo, Bimo Ario; Salleh, Abu Bakar; Abd. Malek, Emilia; Mohd Yahaya, Normi; Abdul Rahman, Mohd Basyaruddin (Springer, 2014)
Peptides mimicked from active site of promiscuous aldo-ketoreductase were synthesized and tested as asymmetry catalysts in the Michael adduct reaction of aldehydes or ketones with nitroolefins to furnish the corresponding γ-nitroaldehydes, γ-nitroketones with up to 93 % yield, 99:1 dr and 71 % ee at room temperature and on eco-friendly solvents. Aspartic acid residue as second amino acid produced greater enantioselectivity.